From Mining Voids to Tourism Villages: Local Educational and Awareness-Based Transformation in Membalong and Tanjung Rusa, Belitung Island - Wulansari, Dini; Sapriyanti, Kiki; Tyas Kencana Putri, Btary (Faculty of Social and Political Sciences University of Bangka Belitung, 2025)
The transition from extractive to sustainable economies represents a complex challenge for post-mining regions in Indonesia. This study explores the emergence and development of locally initiated tourism villages in Membalong and Tanjung Rusa Villages, Belitung, as a model of socio-ecological transformation from tin-extractive landscapes toward creative tourism economies. Employing a qualitative-descriptive approach through in-depth interviews, field observations, participatory mapping, and a literature review and a literature review, this study analyzes the processes of social mobilization, tourism narrative construction, and landscape regeneration undertaken by local communities to transform mining voids (kolong or camui) and environmental degradation into valuable tourism assets. Findings reveal that the success of this model is underpinned by five fundamental pillars: (1) revitalization of post-mining landscapes into tourism lakes and ecological education parks, (2) diversification of environmentally-friendly local products based on pandan thorn handicrafts and natural culinary resources, (3) strengthening of daily cultural practices of gardening and fishing as unique coastal tourism attractions, (4) preservation of hospitable coastal Malay culture as social capital for welcoming tourists, and (5) capacity development in homestay management and tour guiding based on SAPTA PESONA principles (represents Indonesia's seven tourism hospitality standards: safety, order, cleanliness, beauty, friendliness, memorable experiences, and comfort) integrated with enhanced English communication competencies to serve international tourist mobility. However, the sustainability of this model faces critical challenges, including dependency on external support and financing, gaps in community managerial capacity, linguistic competency deficits in communicating with foreign tourists, limitations in effective marketing communication (marcom) strategies to reach broader tourist markets, and risks of pseudo-empowerment in the governance of village-owned enterprises (BUMDes) and tourism awareness groups (Pokdarwis). Theoretically, this study concretizes the concept of community-based tourism (CBT) that not only rehabilitates degraded environments but also cultivates socio-economic and communicative capacities of grassroots communities. The implications position these two villages as case experiences and valuable practical models for other post-mining regions in Indonesia in developing inclusive, competitive, and sustainable destinations.